Leader-Member Exchange as a Moderator of the Relationship between Transformational Leadership and Organization Citizenship Behavior – A case of a multinational hypermarket in Erbil City. - SHERWANI, KARWAN H.; NATHEER, ALI (The journal of contemporary issues in business and government, 2021)
The purpose of this research is to develop a model in which the Leader-member Exchange theory works as a moderator between the Organizational Citizenship Behavior and practices of Transformational Leadership theory. The sample was made up of 92 from managers and employees of Majid Al Futtaim Carrefour Iraq, which is a UAE-based leading retail company in the Middle East, operating in the Kurdistan Region of Iraq. The researchers used a quantitative strategy by conducting a questionnaire of 26 items. To analyze the data, the researchers has used four analytical tools, descriptive analysis, normality distribution, reliability analysis, correlation Analysis, and regression Analysis to test the moderator. In this study, the dependent variable is Organizational Citizenship Behavior, the independent variable is Transformational Leadership, and the moderator is Leader-member Exchange, which is believed to influence the relationship between the independent variable and dependent variable. The findings of the study have evidenced through data analysis and interpretations that Leader- member Exchange as a moderator moderates the relationship between Transformational Leadership and Organizational Citizenship Behaviors to a full extent. The outcomes also suggest the manager who shows transformational leadership styles and establishes a good relationship with the employees, tends to result in better employee citizenship behavior.